Paralympic alpine skiing sitting athletes: trunk muscle activity in giant slalom - Goll, G.; Spitzenpfeil, P.; Beer, K.; Thimm, T.; Bartels, O. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
To gain deeper understanding in the mechanism of elite Paralympic alpine sit-skiing the current study focuses on trunk muscle activity during exercise and alpine skiing. By using a mobile surface electromyography system during giant slalom skiing, the objective of the study was to analyze the individual contribution of three back and one abdominal muscle to this specific movement task.